Bioacústica del canto de anuncio de Ameerega hahneli (Anura: Dendrobatidae) en dos localidades de Loreto, Perú - Aguilar Manihuari, Luis Ramón (2024)
This study focused on comparing the acoustic characteristics of the announcement call of Ameerega hahneli from two localities in Loreto, Iquitos and Yurimaguas. The evaluations were carried out using the methods of visual encounter survey as a free search without restrictions and the active recording of the announcement call of the species. The recordings were made at an approximate distance of 0.5 m from each individual for at least 2 continuous minutes. A Tascam DR-05X handheld recorder with a Sennheisser MK600 unidirectional microphone was used to generate uncompressed 16-bit wav audio files with a sampling rate of 44.1 kHz. The recordings were analyzed with the Raven Pro 1.6.6 program with a Hann-type spectrogram and a window size of 512. 100 songs (notes) from each individual were analyzed, 6 per locality, making a total of 1200 songs analyzed. PCA analyses show two segregated groups, mainly by spectral characteristics; and MANOVA and ANOVA analyses showed a significant difference between localities. In conclusion, there are differences in the acoustic characteristics of A. hahneli between both localities.